Prevalence of hypertension and peripheral arterial disease in adults in Léogâne, Haiti - Joel C Boggan; Schatzi H McCarthy; Jessica E Pritchard; Grant O’Brien; David K Walmer (Journal of Global Health Reports)
# Background